Methodological Analysis of Accounting Quality : Empirical Approach to DeAngelo’s Model and the Modified Jones Model - Denich, Ervin (Public Finance Quarterly, 2021)
The aim of this study is twofold: the first goal is to systemise and summarise the models designed to measure the quality of financial statements, as these reports can form the basis of decision-making for the users. The second goal is to analyse the financial statements prepared by manufacturing companies acting in Baranya Country, from a quality perspective, applying the DeAngelo (1986) model and the modified Jones model (1995). Earnings quality is measured by the change in total accruals divided by total assets, considering a 4-years period of time between 2016 and 2019. Calculating the T-statistic, the amount of total accruals is a negative figure in the covered period. Consequently, it might suggest that managers make some decisions, which have a decreasing impact on earnings level of a company. Although the results of this study show some evidence of earnings management, further investigation is required in order to provide a more confident conclusion.